Clinical Study of Obesity and associated morbidities in patients admitted to College of Medical Sciences Teaching-Hospital, Bharatpur - Pradhan, Manohar (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objectives: The present study was conducted with objective to study the incidence of obesity and associated co-morbidities in patients admitted to CMS-TH, Bharatpur. Materials and Methods: One hundred and fifty consecutive overweight patients from the January 2009 to December 2012 with Basal metabolic index (BMI)>25 and obese patients (BMI>30) were included in this hospital based prospective study. Detailed evaluation of risk factors and family history of other diseases were taken, other obesity related indicators like WPRO, 2000 for BMI, waist circumference (NCEP ATP III and NCEP for South Asian ethnicity) NCEP– National Cholesterol Education Program and waist hip ratio (WHO criteria) were measured and comparison done in order to detect best method for application. These cases were evaluated for associated co-morbid condition and metabolic syndrome which were diagnosed using NCEP ATP III criteria. Results: The mean age of patients was 52.7 years. Commonest co-existing risk factors were alcohol consumption, smoking, hypertension and type 2 diabetes mellitus. Evaluation based on WHO criteria revealed that 56.7% patients were overweight, 38.7 % were obese class II and 4.6 % were class II. While 45.1% male and 69.1% female patients had central obesity. The figure was 81.7 % for males and 94.1% for females with WHO criteria using waist hip ratio. Risk factors like alcohol consumption (52.7%), smoking (52.7%) and fatty liver disease (22.66%) were the commonest co-morbid conditions. Conclusion: In the present study, risk factors of alcohol, smoking and hypertension and co-morbid conditions diabetes mellitus, dyslipidemia, ischemic heart disease, stroke and fatty liver were noted. Waist hip ratio was the best indicator to detect central obesity and co-morbid conditions and recommended to be used for Nepali population. JCMS Nepal. 2015;11(3):16-19